1984
DOI: 10.3109/00016488409132915
|View full text |Cite
|
Sign up to set email alerts
|

The Human Respiratory Nasal Mucosa in Nasal Syphilis:A Histochemical Study

Abstract: The enzymatic changes in tertiary nasal syphilis were studied in 5 patients. The cholinesterase was increased in the subepithelium, around the glands and blood vessels, denoting parasympathetic hyperactivity. Acid phosphatase was increased in the epithelium, stromal histiocytes, around the glands and ducts, indicating increased phagocytotic activity. Alkaline phosphatase was increased in the capillary endothelium and periglandular stroma, denoting marked vascular changes. Succinic dehydrogenase, alkaline phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…9 Steroid hormonlarındaki değişiklikler ile nazal mukozadaki histokimyasal ve ultramikroskobik değişik-likler menstrüel siklus sırasında, gebelikte, oral kontraseptif kullanımında ve menopoz sonrasında araştırılmıştır. [10][11][12] Dişi hormonlarının hangi mekanizma ile nazal fizyolojiyi etkilediği net olmamakla birlikte, progesteron ve östrojen alfa reseptörleri nazal mukozada saptanmamıştır. Ancak, östrojen beta reseptörleri hem erkek hem de dişilerin nazal mukozasında bulunmaktadır.…”
Section: Discussionunclassified
“…9 Steroid hormonlarındaki değişiklikler ile nazal mukozadaki histokimyasal ve ultramikroskobik değişik-likler menstrüel siklus sırasında, gebelikte, oral kontraseptif kullanımında ve menopoz sonrasında araştırılmıştır. [10][11][12] Dişi hormonlarının hangi mekanizma ile nazal fizyolojiyi etkilediği net olmamakla birlikte, progesteron ve östrojen alfa reseptörleri nazal mukozada saptanmamıştır. Ancak, östrojen beta reseptörleri hem erkek hem de dişilerin nazal mukozasında bulunmaktadır.…”
Section: Discussionunclassified
“…The relationship between the hormone estrogen and the nasal mucosa has been postulated by clinical studies that advocate the existence of an entity named hormonal rhinitis, or nasal diseases caused by variations in the hormone levels, especially estrogen, and according to the work of Philpott et al (2004Philpott et al ( , 2008, Shirasaki et al (2004); Toppozada et al (1981Toppozada et al ( , 1982Toppozada et al ( , 1984Toppozada et al ( , 1988 and Zhao et al (2001).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptors (ER) are detectable in the human body tissues, including tissues of reproductive organs, nasal mucosa and nervous system (Ciocca & Roig, 1995;Bowser & Riederer, 2001;Berger et al, 2003;Kuiper et al, 1997;Millas et al, 2011;Philpott et al, 2004Philpott et al, , 2008Shirasaki et al, 2004;Toppozada et al, 1981Toppozada et al, , 1982Toppozada et al, , 1984Toppozada et al, , 1988. To evaluate staining intensity, different methods have been designed as RT-PCR and immunohistochemistry (Bowser & Riederer;Pavao & Traish;Shirasaki et al;Zhao et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Early electromicroscopy studies of nasal mucosae during pregnancy and the menstrual cycle show increased glandular and phagocytic activity and increased mucopolysachharides (18,19) . There is some evidence that nasal physiology does alter with the menstrual cycle.…”
Section: Sex Hormonesmentioning
confidence: 99%
“…Given that nasal mucosa electron microscopy of allergic rhinitics yields an identical picture to that seen in PIR (18) , and the fact that a significant proportion of PIR patients show significant in vitro reactions to house dust mite antigen, it has been suggested that PIR patients represent a subset of subclinical allergic rhinitis. However, these patients will recover from their symptoms spontaneously after delivery, (by definition of true pregnancy induced rhinitis) and serum markers for allergic disease (such as soluble intercellular adhesion molecule-1 (sICAM-1) are not elevated in PIR (32) .…”
Section: Risk Factorsmentioning
confidence: 99%